La satisfacción laboral y su influencia en la productividad de los trabajadores de Sodimac Perú - Trujillo Open Plaza 2013. - Quispe Crisologo, Rose Mary Del Carmen (2014)
The present investigation is aimed at determining the influence of job satisfaction on productivity of workers SODIMAC TRUJILLO OPEN PLAZA 2013 , for which use of seven factors of satisfaction reported by Fernández Ríos became : the financial rewards , the physical conditions of work environment , security and stability offered by the company , relationships with coworkers , support and respect for superiors , recognition by others when needed and the possibility of personal development at work. Field research was used and the information was obtained through a survey applied to a sample of staff to SODIMAC PLAZA OPEN TRUJILLO . Research throw the staff is unhappy , one of the reasons it is considered that they do not receive a fair payment for the work they do. We can also observe that workers SODIMAC PERU SA value security that the company gives them , on the other hand do not perceive a sense of camaraderie and teamwork and feel recognized for the extra effort they make in their work they express that heads not delegate their responsibilities and that their participation does not mark a difference in the organization. SODIMAC associates say PERU SA occupationally feel satisfied improves productivity in the company.